Efficacy and safety of nab-paclitaxel plus platinum in non-small cell lung cancer: a meta-analysis - Tan, Tianying; Li, Shuangshuang; Hu, Wenting; Yue, Tinghui; Zeng, Qi; Zeng, Xingling; Chen, Xiaochao; Zhao, Xiangdong; Xiao, Tianbao (Frontiers in Medicine, 2023)
Purpose: This meta-analysis was exerted in assessing the anti-cancer efficacy and safety of nab-paclitaxel (nab-P) when combined with platinum compound agents for therapy in patients with non-small cell lung cancer (NSCLC). Method: We systematically searched seven electronic databases: PubMed, Cochrane Library, Web of Science, EMBASE, CNKI, Wan Fang, China Science and Technology Journal Data databases. Randomized comparative clinical (RCT) studies on nab-p plus platinum and carboplatin or cisplatin in combination with convention-al chemotherapy agents or traditional paclitaxel were searched. Results: All in all, 19 RCT studies involving 6011 patients were analyzed. The primary outcome including overall response rate (ORR), overall survival (OS) and progression-free survival (PFS), the secondary outcome including adverse events (AEs). Nab-p combined with platinum (carboplatin/cisplatin) for NSCLC had a bet-ter ORR (OR = 1.66, 95% CI [1.34, 2.05], p < 0.001), improved PFS (HR = 0.84, 95% CI [0.74, 0.94], p = 0.01) and OS (HR = 0.86, 95% CI [0.78, 0.96]. p = 0.008) in NSCLC patients. ORR [OR = 2.18, 95% CI (1.07, 4.43)], PFS (HR = 0.62, 95% CI [0.40, 0.97]), OS (HR = 0.63, 95% CI [0.49 0.81]) significantly improved aged >70 and ORR (OR =1.80, 95% CI [1.20, 2.70]), PFS (HR = 0.74, 95% CI [0.56, 0.97]) were significantly elevated with SCC rate ≥ 65% in NSCLC patients (all P > 0.05). Among grade ≥3 of the adverse effects, neutropenia, neuralgia, arthralgia/myalgia were lower toxicities than the control group. Anemia, thrombocytopenia, in nab-P plus platinum (carboplatin, cisplatin) had higher toxicities than controls, in addition, fatigue were no statistical significance. Conclusion: Nab-P in combination with carboplatin, cisplatin regimen is effi-cacy and tolerability for patients with NSCLC.